Tip mendesain realistic interior dengan google sketchup pro 2013 untuk pemula dan awam / Nofrizal ; editor Th. Arie Prabawati. - NOFRIZAL; Arie Prabawati, Th. (Andi, 2014)
xii, 131 hlm. : ilus. ; 21 cm